Empowerment Strategy of Village Enterprises Unit (VEU) to Improve Capacity and Their Performances in Sumedang Regency - Hidayat, Akadun; Sulastri, Lalas (European Journal of Sustainable Development, 2019)
The measurement of VEU performance was difficult because VEU was categorized as Medium, Small and Micro Enterprises (MSMEs). One of the characteristics of MSMEs was the absence of financial statements so that performance was difficult to measure. The VEU classification was very strategic in order to develop the capacity and performance of VEU. This study aims to develop a VEU empowerment strategy to increase capacity and performance 0f VEU in Sumedang Regency. The study used data collection techniques in-depth interviews, observations, and documentation. Triangulation as a technical data analysis, data processing procedures included display data, data reduction, and drawing conclusions. The results showed that VEU performance was influenced by the legality and regulation of VEU governance; manager of entrepreneurial and dedication; mastered accounting and ICT; creating strong leadership; the type of VEU business to fulfill community needs; VEU governance of transparent, accountable, participatory, effective, efficient, and healthy (high liquidity, high profitability, high solvency). The VEU empowerment strategy is carried out by benchmarking, the internal quality assurance system, accreditation, the evaluation of outstanding VEU Managers, and VEU Achievement Assessment. Key Words: governance, healthy, performace, accreditation.